Application ofNevanlinnaTheorytoComplexDifference Equations - Boudaoud MILOUDI (Université de Mostaganem, 2025)
This thesis focuses on the applications of Nevanlinna Theory in studying the uniqueness of meromorphic functions and solutions to complex di¤erence equations. The signi…cant focus in this thesis is on equations derived from meromorphic functions that share speci…c values, particularly those that share a small entire function with their shifts and di¤erence operators, or share a value with two di¤erence operators
Keywords: uniqueness; entire function; meromorphic function; difference operators; di¤erence equations; Nevanlinna theory; exponent of convergence; order of growth